Teknologi Finansial, E-Commerce, Perkembangan Alternatif Pembayaran dan Kinerja Bisnis Toko Online: Suatu Kajian pada Mahasiswa Ekonomi dan Bisnis - Muhammad Rakib; Siti Arafah; Dian Anugrah Sanusi (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
This study aims to reveal the influence of financial technology, e-commerce on the development of payment alternatives and the performance of student online shop businesses. This study uses a type of quantitative research. The research population was all FEB UNM students who were active in the even semester of 2022, namely 3124 people and a sample of 97 respondents, taken by Simple Random Sampling. Data collection techniques were carried out through observation, questionnaires and documentation. The analysis used is multiple regression analysis. The results of the study show that financial technology and E-commerce both simultaneously and partially have a significant influence on payment alternatives and online shop business performance.